A Quaternized Polysulfone Membrane for Zinc-Bromine Redox Flow Battery. (15th May 2014) - Li, Mingqiang; Su, Hang; Qiu, Qinggang; Zhao, Guang; Sun, Yu; Song, Wenjun
Abstract : A quaternized polysulfone (QNPSU) composite membrane is fabricated for zinc-bromine redox flow battery. The structure of the membrane is examined by FT-IR spectra and SEM. The conductivity of the membrane is tested by electrochemical analyzer. After a zinc-bromine battery with this composite membrane is operated at different voltage while charging and at different current while discharging to examine the performance of the membrane, it is found that the discharge voltage was 0.9672 V and the power density was 6 mW/cm 2 at a current of 0.1 A, which indicated that the novel composite membrane is a promising material for the flow battery.